Efektifitas Bimbingan Karir Holland Terhadap Kemandirian Pengambilan Keputusan Pilihan Jurusan DI Perguruan Tinggi Bagi Siswa Kelas XII SMAN 2 Sumatera Barat - Deni Junia Fitri; Masril Masril; Dasril Dasril (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to reveal whether Holland's career guidance is effective for the independence of decision making in choosing majors in tertiary institutions for class XII students of SMAN 2 West Sumatra. In an individual's life, there comes a point where he has to make a decision. Sharing higher-level forms of decision-making, for example regarding life and goals or careers. Every high school student must want or continue their studies at the desired college. Through Holland's career guidance, it is hoped that students or individuals will have preparation in selecting majors at tertiary institutions. This study aims to see the effectiveness of Holland's career guidance on the independence of decision-making in choosing majors in tertiary institutions for class XII students of SMAN 2 West Sumatra. The type of research that the authors use is a pre-experimental study with a one group pretest-posttest design. The data collection technique that researchers use is a questionnaire/instrument. Data processing using SPSS. In this study, the researcher provided classical services regarding Holland's career guidance to respondents who had low decision-making independence in choosing majors. The results of the study can be concluded that Holland's career guidance is effective in increasing the independence of decision-making choices for class XII students at SMAN 2 West Sumatra. This is evident from the results of the t test (paired Simple Test) which obtained sig results that were smaller than the error, so Ho in this study was rejected and Ha was accepted. In the data analysis, it was also seen that there was an increase in the average independence of decision making in the choice of majors given to respondents during the pretest and during the posttest. So it can be concluded that Holland's career guidance is effective in increasing the independence of major decision making for class XII students of SMAN 2 West Sumatra.